PEMBERDAYAAN TERNAK IKAN NILA SISTEM KINCIR AIR HEMAT ENERGI DI KABUPATEN KARANGANYAR - Prihatin, Joko Yunianto; Pambudi, Slamet; Mutaqin, Niki Agastia; Sinatrya, Cahya (Abdi Masya, 2025)
Nila fish is a food source containing animal protein, which is important for human health. The health of nila fish is the main factor that is prioritized by a number of cultivators and livestock breeders. The more quality air in the pond, the more stable the pond temperature will be, and the fish growth will accelerate. The air source comes from nature and is artificial, using a water wheel. The main problem is that the driving engine resource is quite large, 1 pk, which increases operational costs. This activity has the main objective of applying the energy-saving horizontal water mixing technique in fish pond cultivation. The method applied is observation of needs and problems, followed by design and manufacture of tools, and ending with periodic evaluation. The result achieved is that a 1/5 pk energy-efficient water wheel using a gear transmission is able to increase the quality of oxygen content in the tilapia pond.